2011
DOI: 10.1177/003335491112600606
|View full text |Cite
|
Sign up to set email alerts
|

Breast and Cervical Cancer Screening Patterns among American Indian Women at IHS Clinics in Montana and Wyoming

Abstract: Our results are consistent with other surveys among AI women, which report that Healthy People 2010 goals for breast (90%) and cervical (70%) cancer screening have not been met. Improvements in breast and cervical cancer screening among AI women attending IHS facilities are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Travel time was a significant factor for all cancer screenings in this study, which corroborated previous studies that distance and transportation were significant barriers for American Indian communities [6] , [10] , [14] , [20] . Because most American Indians resided in rural areas especially western South Dakota who experienced longer travel time to PCPs as shown in Figure 1a , travel distance poses a barrier to seek primary care services.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Travel time was a significant factor for all cancer screenings in this study, which corroborated previous studies that distance and transportation were significant barriers for American Indian communities [6] , [10] , [14] , [20] . Because most American Indians resided in rural areas especially western South Dakota who experienced longer travel time to PCPs as shown in Figure 1a , travel distance poses a barrier to seek primary care services.…”
Section: Discussionsupporting
confidence: 91%
“…For cervical cancer, this study identified significant barriers that have been proven significant in previous studies, including marital status, age, self-rated health status, whether or not having a PCP, and socioeconomic factors [11] , [15] , [20] .…”
Section: Discussionmentioning
confidence: 81%
“…These differences exist for all age groups and for all cancer screening tests; this is particularly true for immigrant and less acculturated Hispanic women [18,21]. AI women have among the lowest breast and cervical cancer screening rates in the US and this particularly pronounced among AI women in the Southwestern US [20,22,23]. Thus, the benefit of early detection of breast and cervical cancer has been much less apparent among Hispanic and AI populations [8,24].…”
Section: Introductionmentioning
confidence: 99%
“…IRB approval from UW-Madison and the national federal Indian Health Service (IHS) was received. From May to October 2010, healthcare providers (i.e., physicians, nurse practitioners, and physician assistants) who work exclusively with Indigenous patients were recruited in IHS service facilities across the United States, including 15 IHS hospitals, 221 health centers, 34 urban clinics, and 176 Alaska village clinics (Wilson et al, 2011). To help maximize anonymity and expand the study's geographic range of provider representation, IHS headquarters sent a recruitment email to district chief medical officers, who asked clinical directors to forward the message to providers.…”
Section: Study Participantsmentioning
confidence: 99%
“…American Indian Alaska Natives, or as herein referred to, Indigenous populations, experience significantly higher chronic pain rates than other U.S. racial groups (Jimenez, Garroutte, Kundu, Morales, & Buchwald, 2011;Wilson et al, 2011). Pain disparities in Indigenous populations may stem from their shared history of oppression and systemic discrimination, which subsequently set a path toward health disparities for present generations (Evans-Campbell, 2008;Sotero, 2006;Yellow Horse Brave Heart, 2003).…”
Section: Introductionmentioning
confidence: 99%